The Primary Alteration of Ventricular Myocardium Conduction: The Significant Determinant of Left Bundle Branch Block Pattern - Ljuba Bacharova; Bayes de Luna (Cardiology Research and Practice)
Intraventricular conduction disturbances (IVCD) are currently generally accepted as ECG diagnostic categories. They are characterized by defined QRS complex patterns that reflect the abnormalities in the intraventricular sequence of activation that can be caused by pathology in the His-Purkinje conduction system (HP) or ventricular myocardium. However, the current understanding of the IVCD’s underlying mechanism is mostly attributed to HP structural or functional alterations. The involvement of the working ventricular myocardium is only marginally mentioned or not considered. This opinion paper is focused on the alterations of the ventricular working myocardium leading to the most frequent IVCD pattern—the left bundle branch block pattern (LBBB). Recognizing the underlying mechanisms of the LBBB patterns and the involvement of the ventricular working myocardium is of utmost clinical importance, considering a patient’s prognosis and indication for cardiac resynchronization therapy.